Caste and Class Ideology in Contemporary India - Kumar, Vikramendra (New Delhi Rawat Publications, 2025)
Caste and Class Ideology in Contemporary India begins with an overview of major theoretical considerations of caste to elaborate on the genesis, mechanism and the function of the caste system in India. It critically examines the persistence of caste in modern Indian society, challenging the notion that caste is an archaic system compensated for by affirmative action. The book argues that caste continues to function as both a source of discrimination and a structure of advantage, especially in the post-liberalization economy. Drawing on recent research from anthropology, economics, history, and political science, it explores caste$1 (Bs role in social hierarchies, rural inequality, urban labour markets, and the business sector. The author contends that caste perpetuates socio-economic disparities and influences subjective well-being, with its effects travelling from rural to urban areas and across various markets.s
Keywords: Caste-India; Ideology-India; Indian Nationalism